Interaksi Agama dan Politik di Indonesia - A, Akmal; Sianipar, Sunita Br.; Surdikina, Nesi; Hutabarat, Yessica Devina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The relationship between religion and politics in Indonesia is significant and complex, given that Indonesia is the country with the largest Muslim population in the world, yet also has a broad religious diversity. This journal explores the dynamics of the interaction between religion and politics, focusing on contemporary issues such as the role of religion-based political parties, the influence of religion in public policy, and the challenges of pluralism in the democratic era. Through literature analysis and case studies, this journal aims to identify the impacts, challenges, and implications of the interaction between religion and politics in Indonesia. This research finds that religion has a significant influence on Indonesian politics, both through political parties and public policy, but also faces challenges in maintaining pluralism and tolerance. The conclusions and recommendations generated are expected to provide new insights for researchers, policymakers, and the general public in efforts to build an inclusive and tolerant democracy.